Factors Influencing Healthcare Product Purchase Intentions among Gen-Y in Malaysia - Rozuan, Mondari; Azuriaty, Atang; Rossazana, Ab-Rahim; Fadilah, Siali (Human Resource Management Academic Research Society (HRMARS), 2025)
The increasing demand for healthcare products in Malaysia, particularly among Gen-Y, highlights the need to understand the key determinants influencing purchase intentions within this demographic. Grounded in the theory of planned behaviour (TPB), this study investigates the effects of Attitude, Subjective Norms, and Perceived Behavioural Control on Gen-Y’s intention to purchase healthcare products, while integrating additional constructs Promotional Influence and Perceived Price Sensitivity to enhance model robustness. Data was collected through a structured questionnaire distributed to 501 respondents across Malaysia and analysed using SmartPLS 4.0. The findings reveal that Promotional Influence, Subjective Norms, and Perceived Behavioural Control significantly and positively influence purchase intentions, with Promotional Influence emerging as the strongest predictor. In contrast, Attitude and Perceived Price Sensitivity were found to have no significant effect. These results underscore the pivotal role of digital marketing and social influence in shaping Gen-Y’s healthcare purchasing behaviour, suggesting that marketers and policymakers must tailor strategies that emphasize promotional channels and enhance perceived behavioural control to stimulate proactive healthcare engagement. This study contributes both theoretically by extending TPB and practically by informing targeted marketing approaches for health-related products in Malaysia.